Using TPACK To Design Local Wisdom-Based Literature Appreciation Learning in the Digital Era - Dina Mardiana; Simpun Simpun; Orbit Thomas (LPPM Universitas PGRI Sumatera Barat, 2023)
This research was motivated by the low value of student learning outcomes in designing Indonesian literature appreciation learning based on local wisdom in the digital era. In fact, integrating digital technology into learning has become part of students' competence as prospective 21st century learning teachers. The aim of this research is to improve students' ability to design Indonesian literature appreciation learning based on local wisdom in the digital era by applying the TPACK concept. The classroom action research method using Kurt Lewin's four-step model was applied in this research. The research subjects were 40 fourth semester students at the Primary School Teacher Education (PGSD) Study Program at Palangka Raya University. The research results show the success of increasing student learning outcomes which is very significant. In the pre-action stage the average student score was still at 57.5 with 12.5% completion, after the action in cycle I the student score reached an average of 71.25 with a completion percentage of 75% and after the action in In cycle II, the average student score reached 80 with a completion percentage of 92.5%. In conclusion, the TPACK concept applied by the lecturer team during class action was able to increase student learning achievement scores by 22.5 and increase the percentage of completion by up to 80%.